الأحزاب السياسية في المنطقة العربية: بحث في مقاربات الازمة وامكانية اصلاح الاختلالات - زريق نفيسة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تسعى الدراسة للوقوف على أهم عناصر الأزمة البنيوية للأحزاب السياسية في المنطقة العربية، وفق مقاربات تبحث في الامتداد التاريخي للأزمة ودور النظام السلطوي في تعطيل العمل الحزبي، إلى جانب الموروث الثقافي للمجتمعات العربية الذي يرفض في العمق الثقة في العمل الحزبي، بما أسهم في بناء تعددية حزبية فشلت في أن تكون جزء من تعددية سياسية، وفي تجاوز مختلف الأمراض التي تنخر الجسم السياسي. وكيف ساهم ذلك في ضٌعف فاعليتها السياسية والتنظيمية وكذا انحسار تأثيرها في المنعطفات التاريخية الكبرى. Abstract: The study aims at identifying the most important elements of the political parties’ structural crisis In the Arab region, according to approaches, it examines the historical extension of the crisis and the role of the authoritarian regime in disrupting partisan action. In addition to the cultural heritage of Arab societies, which in depth rejects confidence in party work, which contributed to the building of party pluralism that failed to be part of a political pluralism , and transcending the various diseases that derate the political body. How this has contributed to their weak political and organizational effectiveness as well as to their decline Its impact on historical turns.